Multimodality Characterization of the Clot in Acute Stroke - LaGrange, Daniela Dumitriu; Wanke, Isabel; Machi, Paolo; Bernava, Gianmarco; Vargas, Maria; Botta, Daniele; Berberat, Jatta; Muster, Michel; Platon, Alexandra; Poletti, Pierre-Alexandre; Lövblad, Karl-Olof (Frontiers in Neurology, 2021)
Aim: Current treatment of occluded cerebral vessels can be done by a variety of endovascular techniques. Sometimes, the clot responds in varying degrees to the treatment chosen. The Ex vivo characterization of the clot occluding the arteries in acute ischemic stroke can help in understanding the underlying imaging features obtained from pre-treatment brain scans. For this reason, we explored the potential of microCT when combined with electron microscopy for clot characterization. Results were compared to the clinical CT findings. Methods: 16 patients (9 males, 8 females, age range 54–93 years) who were referred to our institution for acute stroke underwent dual-source CT. Results: Clinical CT clots were seen as either iso or hyperdense. This was corroborated with micro-CT, and electron microscopy can show the detailed composition. Conclusion: MicroCT values can be used as an indicator for red blood cells-rich composition of clots. Meaningful information regarding the clot composition and modalities of embedding along the stent retrievers can be obtained through a combination of microCT and electron microscopy.